2000
DOI: 10.1093/sw/45.2.157
|View full text |Cite
|
Sign up to set email alerts
|

A Topography of Self-Help Groups: An Empirical Analysis

Abstract: The current managed health care system creates an environment in which social workers need to be knowledgeable about low-cost interventions. Self-help groups have the potential to be beneficial to social workers' clients. Surprisingly, little is known about the characteristics and activities of many groups and the extent to which groups receive guidance and support from professionals and established national and local organizations. Whereas many social workers are aware of Alcoholics Anonymous (AA), there are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
6

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 12 publications
0
23
0
6
Order By: Relevance
“…They can also learn and practise problem‐solving skills by being involved in group activities. As an empowerment‐oriented intervention, mutual support groups provide opportunities for family caregivers to develop knowledge and skills of caring for a relative with schizophrenia with peer support, establishing a harmonious family life, and engaging professionals as collaborators instead of authoritative experts (Perkins & Zimmerman 1995, Wituk et al. 2000).…”
Section: Discussionmentioning
confidence: 99%
“…They can also learn and practise problem‐solving skills by being involved in group activities. As an empowerment‐oriented intervention, mutual support groups provide opportunities for family caregivers to develop knowledge and skills of caring for a relative with schizophrenia with peer support, establishing a harmonious family life, and engaging professionals as collaborators instead of authoritative experts (Perkins & Zimmerman 1995, Wituk et al. 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Leaders argued that formal provision of funding would increase group recognition and credibility amongst key stakeholders, thereby increasing the referral of new patients to the group and reducing fluctuations in group membership. The referral of new members and maintenance of adequate numbers at the regular group meeting has been previously found to best differentiate between active and disbanded self-help groups [15,16]. Strategies to encourage more trust and contact between medical staff and support groups, particularly those operating outside the formal health system, are required.…”
Section: Discussionmentioning
confidence: 99%
“…With specific reference to Hong Kong, a review of the psychiatric rehabilitation system (Yip 1996, 1997, Mak & Yip 1997 shows it lacks structured rehabilitation programmes, especially the informal community programmes based on the 'self-help group' (SHG) approach. Although empirical research of SHG in health-related group is limited, most local and overseas studies have shown to be remarkably effective in promoting the recovery and rehabilitation of persons who share common problems (Ma 1992, Humphreys & Noke 1997, Wituk et al 2000, Mok 2001, Clay 2005. Furthermore, with the exception of the gospel drug rehabilitation programmes (e.g., Ng & Shek 2001), the spiritual element is not consciously included in most of the psychiatric rehabilitation programmes.…”
Section: Introductionmentioning
confidence: 99%